MAGGOT INFESTATION IN CIRCUMCISION WOUND: A CASE REPORT AND REVIEW OF LITERATURE - Ishrat Mahtam; Soomro, Sirajuddin; Roshan Ali Siyal; Baqa Muhammad Abbasi (Journal of Ayub Medical College Abbottabad, 2025)
Back Ground: Male circumcision is an obligated practice in Muslims and Jews and it is one of the oldest operations performed all over the world. The safety of male circumcision depends on various factors including the who circumcised the boy, the type of anesthesia used and associated complications. Circumcision in Pakistan is mainly done by traditional circumcisers and less by medically trained professionals. The various complications associated with circumcision include bleeding, excessive or inadequate removal of fore skin, injury to the glans and infection. Myasis of circumcision wound is an extremely rare event.